An Effective Method for the Preparation of Stable LC Composites with High Concentration of Quantum Dots. Issue 12 (7th November 2014) - Bobrovsky, Alexey; Samokhvalov, Pavel; Shibaev, Valery
<x xml:space="preserve">Abstract</x> The effective method of preparation of hybrid organic–inorganic multifunctional liquid crystalline (LC) composites with a high content of QDs is elaborated. The obtained QD–LC composites possess very bright circularly polarized fluorescence. The absence of quantum dot aggregates and a high degree of circular polarization of emission make these composites promising for different applications in photonics. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>